FINANCING RISK MEASUREMENT WITH MAQASHID AL-SHARIA QUALITATIVE RISK - A. Syathir Sofyan; Salmah Said; Muhammad Wahyuddin Abdullah (Share: Jurnal Ekonomi dan Keuangan Islam, 2019)
Measurement of financing risk has been dominated by quantitative methods, which insufficiently pay attention to the detailed causes of default risk. So far, the concept of mafsadah in maqashid al-sharia has never been applied in risk management. Thus, the aim of this study is to measure the risk of financing with the qualitative risk assessment method based on maqashid al-sharia by proposing the use of the mafsadah matrix. This research applies qualitative method equipped with a phenomenological approach as observed in Islamic financial institutions in Makassar. Data collection was carried out by observation and interviews with the branch heads, credit analysts, and staff of the Islamic financial institutions. Data analysis and interpretation technique are in line with Miles and Huberman analysis with three stages, namely data reduction, data presentation, and data verification. This study found that there were seventeen risk events with the level of mafsadah tahsiniyyat as many as four events, mafsadah hajiyyyat as many as four events, and mafsadah dharuriyyat as many as nine events. In addition, this research reveals that customers, indeed, fail to pay due to their bad characters and moral hazards (mafsadah dharuriyyat) resulting in liquidity problems in Islamic financial institutions. This is due to the misappropriation of credit committee approval and unresponsive handling of bad financing (mafsadah dharuriyyat) resulting in delays in Islamic financial institutions to further process financing proposals (mafsadah dharuriyyat).==============================================================================================Pengukuran Risiko Pembiayaan dengan Maqashid al-Syariah Qualitative Risk. Pengukuran risiko pembiayaan telah didominasi metode kuantitiatif yang kurang memerhatikan penyebab terjadinya default risk secara detail. Selama ini, konsep mafsadah dalam maqashid al-syariah belum pernah diaplikasikan dalam aspek manajemen risiko. Maka, tujuan penelitian ini adalah untuk mengukur risiko pembiayaan dengan metode qualitative risk assessment yang berbasis maqashid al-syariah dengan menggunakan matriks mafsadah. Penelitian ini adalah penelitian kualitatif dengan pendekatan fenomenologi pada lembaga pembiayaan syariah di Makassar.  Pengumpulan data dilakukan dengan observasi dan wawancara terhadap kepala cabang, credit analyst, dan staf karyawan lembaga pembiayaan syariah. Teknik analisis dan interpretasi data menggunakan analisis Miles dan Huberman dengan tiga tahapan, yaitu reduksi data, penyajian data, dan verifikasi data. Penelitian ini menemukan terdapat tujuh belas peristiwa risiko dengan tingkatan mafsadah tahsiniyat sebanyak empat peristiwa, mafsadah hajiyat sebanyak empat peristiwa, dan mafsadah dharuriyat sebanyak sembilan peristiwa. Selain itu, penelitian ini mengungkap bahwa peristiwa nasabah gagal bayar karena karakter buruk dan moral hazard (mafsadah dharuriyat) mengakibatkan masalah likuiditas pada lembaga pembiayaan syariah. Hal ini disebabkan kekeliruan persetujuan pembiayaan oleh credit committee dan penanganan yang tidak responsif atas pembiayaan macet (mafsadah dharuriyat) berakibat keterlambatan lembaga pembiayaan syariah memeroses pengajuan pembiayaan (mafsadah dharuriyat).